Integrasi Pengajaran Bahasa Inggris dalam Projek Penguatan Profil Pelajar Pancasila (P5) Guna Mendukung Implementasi Kurikulum Merdeka di TK DWP Kenongo - Wilujeng, Lilis Lestari; Susilowati, Meme (Abdimas Indonesian Journal, 2025)
As a pioneering school, TK DWP Kenongo must begin implementing the Kurikulum Merdeka. One key program to be carried out is the Projek Penguatan Profil Pelajar Pancasila (P5). At the early childhood education level, teachers are encouraged to independently develop teaching modules, project modules, and learning materials by utilizing available resources around them. Given the flexible nature of the curriculum, teachers have the freedom to develop learning methods aligned with their vision and mission. One of these is the incorporation of basic English language introduction as a local content subject. With the implementation of Kurikulum Merdeka, they aim to integrate basic English language learning within the curriculum. Therefore, assistance in integrating these two aspects is highly needed. To address this issue, the proposing team initiates a solution by identifying existing materials and integrating them with basic English introduction for students. This approach ensures that the Kurikulum Merdeka, which is based on four main themes, and English language instruction can run simultaneously, aligning with students' developmental stages. After identifying the core issues and available resources, the proposed program includes training and mentoring for integrating English language instruction into relevant P5 activities, along with classroom implementation support. The solution focuses on two key aspects: training and mentoring for the implementation of the Aku Cinta Indonesia teaching module integrated into P5. As a result, the program objectives are achieved, leading to an improvement in teachers' skills in teaching English in alignment with Kurikulum Merdeka.